Two new species and four new records of Diduga (Lepidoptera, Erebidae, Arctiinae) from Laos - Bayarsaikhan, Ulziijargal; Cha, Yeong-Bin; Lee, Tak-Gi; Jang, Chang-Moon; Kwon, Hyung Wook; Bae, Yang-Seop (Zootaxa, 2021)
Two new species, Diduga hastata sp. nov. and Diduga mucronata sp. nov. are described from Laos along with four newly recorded species, D. annulata Hampson, 1900, D. amoenusa Bucsek, 2012, D. allodubatolovi Bayarsaikhan, Li & Bae, 2020 and D. luteogibbosa Bayarsaikhan, Li & Bae, 2020. Illustrations of adults and genitalia of examined species from Laos are provided.